El hábeas corpus correctivo y el principio de interculturalidad en la ejecución de la pena. - Fiallos Guachilema, Ramiro Gustavo (2025)
The current study examines whether corrective habeas corpus is useful as a legal mechanism for recognizing the principle of interculturality in the implementation of criminal sentences. Specifically, it explores corrective habeas corpus potential to protect the cultural dimension of personal integrity for Indigenous people deprived of liberty, particularly when their convictions lack explicit recognition of interculturality—thus preventing access to culturally appropriate, community-based rehabilitation programs. Using a qualitative methodology, the research employs juridical-analytical, dogmatic, descriptive, and case study methods. The analysis draws primarily on Ecuador’s Constitutional Court ruling 112-14-JH/21 and a practical case in Riobamba. Structured interviews were conducted with five experts in Constitutional and Criminal Law, and their insights were analyzed through qualitative coding. The findings indicate that the immutability of criminal judgments often precludes the implementation of intercultural measures during incarceration when not originally recognized by the court. However, expert testimony suggests that corrective habeas corpus may offer a viable legal remedy to address this procedural omission. The study identifies a significant gap between the formal recognition of interculturality and its practical enforcement within the justice system. It concludes that corrective habeas corpus can facilitate the recognition and application of intercultural principles in sentence execution. Nevertheless, the research underscores the need to expand the legal scope of this remedy and to enhance the training of judicial actors in collective rights, to ensure culturally appropriate justice for Indigenous peoples and nationalities